Is C50 a superaromat? Evidence from electronic structure and ring current calculations. Issue 17 (7th October 2015) - Matías, Ana Sanz; Havenith, Remco W. A.; Alcamí, Manuel; Ceulemans, Arnout
Abstract : Of the three lowest isomers of C50 fullerene, the minimal energy D 3 isomer comes closest to a spherical aromat or superaromat. Abstract : The fullerene-50 is a 'magic number' cage according to the 2( N + 1) 2 rule. For the three lowest isomers of C50 with trigonal and pentagonal symmetries, we calculate the sphericity index, the spherical parentage of the occupied π-orbitals, and the current density in an applied magnetic field. The minimal energy isomer, with D 3 symmetry, comes closest to a spherical aromat or a superaromat. In the D 5h bond-stretch isomers the electronic structure shows larger deviations from the ideal spherical shells, with hybridisation or even reversal of spherical parentages. It is shown that relative stabilities of fullerene cages do not correlate well with aromaticity, unlike the magnetic properties which are very sensitive indicators of spherical aromaticity. Superaromatic diamagnetism in the D 3 cage is characterized by global diatropic currents, which encircle the whole cage. The breakdown of sphericity in the D 5h cages gives rise to local paratropic countercurrents.